TYPP : #6. - Van Beek, Jozefien; Dumalin, Caroline; Garabedian, Mekhitar; Kubat, Zeynep; Van der Gucht, Saskia (Antwerp : KdG / St Lucas School of Arts)
Larissa Cluzet: Mega container ship loses 270 containers in the North Sea ; Robin Vanbesien: On 'In a world for all of us!' ; Steve Van den Bosch: Ignore this page ; Liesbeth Den Besten: Disruptors: Contemporary jewels and the essence of jewellery ; Cleo Foole, Dexian Feng, Elena Op 'T Eynde, Tim Verherstraeten: TIM
boek